Pengaruh Reputasi, Budaya, dan Pengetahuan terhadap Niat mengunjungi Pariwisata Kota Medan - Zulkarnain (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to analyze the influence of reputation, culture, and knowledge on tourists' intention to visit Medan City tourism. Using a quantitative approach, this research involved 210 respondents selected through purposive sampling technique. Data were collected using a structured questionnaire with a 5-point Likert scale and analyzed using descriptive statistical methods, correlation analysis, multiple linear regression, and Structural Equation Modeling (SEM). Descriptive analysis results showed highly positive perceptions toward all research variables, with mean values above 4 out of 5. Correlation analysis revealed strong relationships between variables, with perfect correlation (1.00) between culture and knowledge variables. Regression and SEM results indicated that all independent variables had positive and significant effects on visit intention, with culture/knowledge factor having a stronger influence (β = 0.512, p < 0.001) compared to reputation (β = 0.275, p < 0.001). The research model demonstrated good fit indices (CFI = 0.956, RMSEA = 0.068) and explained 53.4% of the variation in visit intention. These findings imply the importance of tourism development strategies that emphasize cultural aspects and tourist education, while maintaining Medan City's reputation management as a tourist destination. This research contributes theoretically to understanding factors influencing tourists' visit intention and practically to the development of Medan City's tourism strategies.